Glimpse on 21st century new phobias; a predictive model of nomophobia - Ceobanu, Ciprian Marius; Marian, Andrei Lucian; Apostolache, Roxana (Frontiers in Public Health, 2023)
The main purpose of this study was to examine the explanatory power of a predictive model of nomophobia consisting of rumination, fear of missing out (FoMO), mindfulness and non-pathological compulsions. The research involved a cross-sectional design exploring the prevalence of nomophobia in a Romanian university students’ cohort. The quantitative methodology was used to collect and analyse the data obtained from all the respondents. Researchers adapted and pretested the questionnaire NMP-Q, before distributing it to 194 university students. SPSS (V. 20) and Hayes’s PROCESS tool were used to analyse the data. The findings demonstrated that the above-mentioned psychological variables have a direct and significant relationship with nomophobia. Specifically, within the multidimensional mechanism that explains nomophobia, fear of missing out (FoMO), non-pathological compulsions, and rumination, included in the predictive model in this order, played the most important role, as together cover 34% of nomophobia variance. Furthermore, the fear of missing out has the highest explanatory contribution to nomophobia. The current study gives a better understanding of the dynamics of nomophobia in young people by focusing on psychological factors that play an important role in this phenomenon.